Penerapan Manajemen Resiko pada Pembiayaan Mudharabah di PT. BPRS Gebu Prima - Arianti, Cindy; Nasution, Salman (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to find out how PT BPRS Gebu Prima manages risks related to mudharabah financing and problematic financing. This research is qualitative in nature, and data was collected through direct observation and interviews. The analysts obtained the exploration results directly by following mudharabah support exercises conducted at PT BPRS Gebu Prima. Board risk at this bank is resolved in three stages, the first is the planning stage which includes the exercise of ending the connection and actually looking at the client's upcoming reporting needs. The next stage is the execution stage which contains study exercises and supporting examinations by the Bookkeeper who pays attention to the 5C standards (Character, Limit, Capital, Assurances and Conditions). Apart from that, the control stage which includes monitoring activities on the use of financing and installments is the third stage. Many studies have been published regarding the risks associated with profit sharing schemes, one of which is the result that a normative approach to risk management in profit sharing systems is needed.